IMPLEMENTATION OF SDGS ON THE GOAL OF QUALITY VILLAGE EDUCATION IN SRI MULYA VILLAGE, SINAR PENINJUAN DISTRICT, OKU REGENCY, SOUTH SUMATERA PROVINCE - Purnamasari, Diah Ayu; Shobaruddin, Muhammad; Domai, Tjahjanulin (Faculty of Administrative Science, Universitas Brawijaya, 2024)
The purpose of this village sustainable development research is to describe how the implementation of SDGs on the goal of quality village education in Sri Mulya Village. This type of research is qualitative descriptive. This study looks at the implementation of village SDGs on the goal of quality village education by looking at the SDGs score on the goal of quality village education. The results of this study indicate that the implementation of village SDGs on the goal of quality village education is not optimal. The suboptimal results can be seen from the lack of synchronization between the data on the Ministry of Villages website and those in the field. This shows that data updating is not optimal so that data updating needs to be improved.